328 The Potential Role of Two Red Seaweeds That Promote Anti-methanogenic Activity and Rumen Fermentation Profiles Under Laboratory Conditions. (8th October 2021) - Min, Byeng Ryel; Genovese, Giusi; Castleberry, Lana; Lockard, Cathy; Waldrip, Heidi; Miller, Daniel; Akbay, Alexia; Morabito, Marina; Manghisi, Antonio; Spagnuolo, Damiano; Brauer, David
Abstract: Ruminal methane (CH4 ) production results from carbohydrate fermentation by ruminal microbiota (methanogens) to produce CH4, volatile fatty acids (VFA), carbon dioxide (CO2 ), nitrous oxide (N2 O), and hydrogen (H2 ) in a reduction pathway. The aims of this study were to assess the effects of two red seaweed (RSW) species (Asparagopsis taxiformis and A. armata; collected from Messina, Italy). The two RSW were identified by DNA barcoding and genetic data were deposited in BOLD Systems (REAPP006-21, REAPP004-21, respectively). The two RSW were used at dietary inclusion levels (0, 2, and 4% as-fed basis) in an anaerobic in vitro study (39°C for 48-h) to examine greenhouse gas (GHG) production and VFA profiles. Gases were collected using an ANKOM Gas Production system and analyzed for CH4 and N2 O by gas chromatography. Asparagopsis taxiformis contained higher levels of bromoform (201 vs. 7.0 mg/kg DM), iodine (4820 vs. 3260 ppm), and crude protein (16 vs. 15.6% DM), than A. armata, which contained higher levels of acid detergent fiber (ADF; 7.7 vs. 19.0%) and neutral detergent fiber (NDF; 13.2 vs. 19.2%), respectively. RSW supplementation increased total gas, butyrate and valerate production (P < 0.01), while production of CH4 (mg/g DM), acetate (A), propionate (P), A/P ratios and in vitro dry matter digestibility (IVDMD; % DM) were reduced (P < 0.01) as RSW supplementation increased. In the presence of A. taxiformis, production of N2 O (µg/g DM), tended to be less (P = 0.1) at 2% DM, but increased (P < 0.01) N2 O production with A. armata at the 2 and 4% DM. Therefore, it may be possible to suppress methanogenesis both directly and indirectly by addition of RSW. To efficiently use seaweeds as feed ingredients with nutritional and environmental benefits, more research is required to determine the mechanisms underlying seaweed and dietary substrate interactions.